Management of enterprise development in the conditions of innovative knowledge-oriented economy - Мартиненко, М. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The article determines a significant importance of knowledge management as a key technology for the development of an enterprise in an innovative knowledge-based economy. The main features of the enterprise development as an open dynamic system are systematized and characteristics of the knowledge economy and innovative economy are determined. Following the above characteristics it is proved that the formation of an innovative economy is impossible without new knowledge and its commercialization, and the basis of the knowledge economy are innovations in various fields of activity. The given types of economies should be further considered not as separate concepts, but as integral components of the innovative knowledge-based economy. The theoretical approaches to the definition of the essence of knowledge management at the enterprise are systematized and their interrelation with the innovation process and innovative development is shown through the creation of new knowledge, increasing the efficiency of innovation development and the formation of innovative abilities of the innovatively active employees. The goals, tasks, functions, principles, stages, methods and methods of knowledge management in innovative knowledge-based economy are considered. The typology of contradictions in the innovative activity of the enterprise is given; the essence of economic, information, technological, organizational, psychological, structural and social contradictions is revealed. Technologies of knowledge management that contribute to eliminating contradictions and innovative development of the enterprise are defined. It is substantiated that different types of contradictions in the innovative activity of an enterprise can be eliminated by means of knowledge management technologies, which, as a result, causes qualitative changes at the enterprise. As the key signs of development are qualitative changes and elimination of contradictions, the use of knowledge management in the conditions of an innovative knowledge-based economy will contribute to the development of the enterprise.